2011
DOI: 10.1523/jneurosci.5616-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

PSD-95 and PSD-93 Play Critical But Distinct Roles in Synaptic Scaling Up and Down

Abstract: Synaptic scaling stabilizes neuronal firing through the homeostatic regulation of postsynaptic strength, but the mechanisms by which chronic changes in activity lead to bidirectional adjustments in synaptic AMPAR abundance are incompletely understood. Further, it remains unclear to what extent scaling up and scaling down utilize distinct molecular machinery. PSD-95 is a scaffold protein proposed to serve as a binding “slot” that determines synaptic AMPAR content, and synaptic PSD-95 abundance is regulated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
99
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 51 publications
13
99
1
Order By: Relevance
“…This is consistent with our previous finding that PSD-95 knockdown reduces metabotropic excitatory postsynaptic current frequency in old but not young neurons [29]. Between DIV 7 and DIV 14 the levels of synaptic PSD-95 increase substantially [28,29], and it has been shown that postsynaptic densities share and compete for PSD-95 [5,7]. As the acquisition of PSD-95 is probably regulated by changes in activity and experience [5, 45,46] when PSD-95 levels are low early in development, competition for PSD-95 could help determine which synapses are maintained and which are lost.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This is consistent with our previous finding that PSD-95 knockdown reduces metabotropic excitatory postsynaptic current frequency in old but not young neurons [29]. Between DIV 7 and DIV 14 the levels of synaptic PSD-95 increase substantially [28,29], and it has been shown that postsynaptic densities share and compete for PSD-95 [5,7]. As the acquisition of PSD-95 is probably regulated by changes in activity and experience [5, 45,46] when PSD-95 levels are low early in development, competition for PSD-95 could help determine which synapses are maintained and which are lost.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with our previous finding that PSD-95 knockdown reduces metabotropic excitatory postsynaptic current frequency in old but not young neurons [29]. Between DIV 7 and DIV 14 the levels of synaptic PSD-95 increase substantially [28,29], and it has been shown that postsynaptic densities share and compete for PSD-95 [5,7].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations